Bibliometric Analysis of Urban Farming - Loso Judijanto; Bintang Cahya; Rani Eka Arini (Westscience Press, 2026)
Urban farming has emerged as an important research area in response to increasing urbanization, food security challenges, and the need for sustainable agricultural systems. This study aims to examine the development, intellectual structure, collaboration patterns, and emerging research trends in urban farming literature using a bibliometric analysis approach. Data were collected from the Scopus database using relevant keywords related to urban farming and analyzed through performance analysis and science mapping techniques with VOSviewer. The analysis covers publication trends, highly cited literature, author collaboration, institutional and country networks, keyword co-occurrence, temporal evolution, and research density patterns. The findings indicate that urban farming research has evolved from a focus on peri-urban agriculture, land utilization, and sustainable food production toward technology-driven approaches involving vertical farming, hydroponics, smart agriculture, Internet of Things (IoT), artificial intelligence, and machine learning. The collaboration analysis reveals that urban farming research is globally distributed, with countries such as Indonesia, the United States, China, India, Germany, and the United Kingdom serving as important knowledge contributors. The keyword analysis further demonstrates that sustainability, food security, and technological innovation represent the dominant themes shaping the field. This study contributes to a better understanding of the intellectual development of urban farming research and identifies future opportunities for integrating digital technologies, sustainability strategies, and inclusive urban agricultural policies.